2015
DOI: 10.1645/15-754.1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Mesenchymal Stem Cells on Early and Late Experimental Hepatic Schistosomiasis Model

Abstract: Cell-based therapy is emerging as a promising therapeutic approach for a wide range of liver diseases. This study aimed to investigate the regenerative and antifibrotic therapeutic potential of bone marrow-derived mesenchymal stem cells (BM-MSCs) in an early and late experimental hepatic schistosomiasis model. BM-MSCs were isolated from 6-wk-old BALB/c donor male mice, then grown and propagated in culture until cell count was 5-8 × 10(6)/ml. MSCs were then separated and injected into Schistosoma mansoni -infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs) represent a promising therapeutic strategy for schistosome-induced liver injury [6][7][8][9][10], but this approach has been hindered by a limited understanding of the MSC-mediated control of liver injury in schistosomiasis. Extracellular vesicles (EVs) are small membrane vesicles released by almost all cell types, which contribute to donor cell-mediated biological effects [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) represent a promising therapeutic strategy for schistosome-induced liver injury [6][7][8][9][10], but this approach has been hindered by a limited understanding of the MSC-mediated control of liver injury in schistosomiasis. Extracellular vesicles (EVs) are small membrane vesicles released by almost all cell types, which contribute to donor cell-mediated biological effects [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, based on widely anti-inflammatory effects, MSC has been employed to attenuate hepatic fibrosis induced by Schistosoma infection, and in parallel with the decreased hepatic stellate cell (HSC) activation and enhanced liver regeneration [5][6][7]. However, the effects of MSC on T cells, especially on Th1/Th2 modulation in this model, are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It also enhances the cost benefit effectiveness and support the idea of xenogenic MSCs therapy trials in humans. This xenogenic transplantation was previously done with success by different authors who reported successful survival of xenogenic MSCs [17,31].…”
Section: Discussionmentioning
confidence: 99%
“…When cultures become confluent, the cultures were treated with 2 ml of 0.25 % trypsin/0.02 % EDTA for 2 min at 37 O C to detach cells from the flasks. Trypan blue was used to test the viability of cells, and then a hemocytometer was used to count the cells and adjusted to 10 6 cells /ml, then used immediately for animal treatment [17].…”
Section: Isolation and Culture Of Bm-mscsmentioning
confidence: 99%